Investigation of the Epidemiological Trend of Cutaneous Leishmaniasis in Patients Referring to the Division of Health Center of Gerash (South of Fars Province) during 2007-2020 - Hajar Haghshenas; Hakimeh Akbari; Mohammad Nowrouzi; Akbar Mehralizadeh; Gholam Ali Haghighat (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: Cutaneous leishmaniasis (CL) is one of the Zoonotic parasitic diseases caused by protozoa of the genus leishmania. This disease is prevalent in many parts of the world, particularly in Iran. The present study aimed to assess the trend of CL in Gerash, Iran, during 2007-2020. Methods: This study was conducted based on a secondary design. The following data were collected: patient's age, gender, number and location of sores, disease type and reservoir, place of residence, and type of Construction. The obtained data were analyzed in SPSS software (version 24). Results: Out of 562 patients, 276 cases were male, and 286 subjects were female. Cutaneous Leishmaniasis was diagnosed clinically and based on laboratory tests in 48.6% and 51.4% of the cases, respectively. The highest and lowest prevalence rates were detected in the age groups of below 10, and over 61 years, respectively. The highest frequency of lesions was in patients with urban leishmaniasis and the most affected areas were hand and face (30.56%).  Moreover, 66% and 34% of patients were infected with urban and rural types of disease, respectively. Furthermore, 61.21% of patients were living in newly-built houses, and the rest were residing in old buildings. In addition, 33% and 67% of them resided in rural and urban areas, respectively. Conclusion: Due to the high prevalence of CL in Gerash and its increase in 2017, there is a need for coherent planning and effective health measures by the officials of different organizations and public participation to prevent the spread of this disease